Características morfometricas físico-químicas del guanchiche (hoplias spp) en Los Rios Quevedo, Babahoyo y la Represa Daule Peripa situados en la costa Ecuatoriana. - Pazmiño Macías, Johnny Jonathan (2016)
The present investigation was carried out in three sites of the Ecuadorian coast and in the experimental farm "The Maria" belonging to Quevedo State Technical University (UTEQ), located at km 7 of the Quevedo - El Empalme road. Morphometric characteristics were evaluated and physical-chemical analyzes were performed, with the following treatments: (T1) Rio Quevedo with 60 specimens (guanchiches); (T2) Rio Babahoyo with 60 specimens (guanchiches), (T3) Daule Peripa dam with 60 specimens (guanchiches). A Completely Random Design (DCA) was used, with three treatments and ten replications that had six fish. The variables evaluated were: weight in grams, total length, standard length, head length, predorsal length, preanal length, upper jaw length, caudal fin base height, eye diameter. We used 180 guanchiches, with an average weight of 250 gr. In the weight-in-grams variable, if significant differences were found between treatments according to the Tukey's test (p <0.05), the treatment with the highest weight in grams average was the (T3) with 470 grams, while the average total length (T1) with 29.54. In the variable preanal length there are no significant differences between treatments according to the Tukey test (p> 0.05). In the standard length variable there were no significant differences between treatments according to the Tukey's test (p <0.05), the treatment with the highest upper jaw length was the (T3) with 1.99cm and the shortest length Upper jaw was the (T2) with 1.30. In the variable predorsal length if significant differences were found between treatments according to Tukey's test (p <0.05)